LA “PIANTA TOPOGRAFICA DELLA ZONA ARCHEOLOGICA DI ROMA. ESEMPIO DI UNIONE DI TRE LEVATE CONSECUTIVE” (1909) - Castrianni, Laura (GEOmedia, 2023)
The photomosaic of the central archaeological area of Rome, result of the union of three consecutive shots, carried out in 1909 by the Aerostieri of the Specialist Brigade of Military Engineers, guided by Captain Cesare Tardivo, represents - together with the slightly later photomosaics of Ostia (1910) and Pompeii (1911) - one of the first experiments in application of the newborn aerophotographic science to archeology and at the same time an exceptional document of the historical palimpsest of the area between the Colosseum and the Campidoglio. It is composed by a sequence of shots taken from a braked balloon made available by the Military Engineers, and it was presented for the first time by Tardivo himself at the International Congress of Photography in Brussels in 1910. It testifies the progress of the stratigraphic excavations taken in those years, with rigorous scientific method, by Giacomo Boni, as Director of the Roman Forum and Palatine Hill. It also represents a precious testimony of the aspect that the area must have had before the demolitions of the 1920s and 1930s, aime at the opening of Via dei Fori Imperiali, and of the deep urban transformations following the building of the Monument to king Vittorio Emanuele II (Vittoriano), then still under construction.